2022
DOI: 10.52184/isbrmj.v6i02.117
|View full text |Cite
|
Sign up to set email alerts
|

Causality Exploration of Paradigm shift in people preferences to OTT Platforms during pandemic: A Mixed Study

Abstract: The COVID-19 pandemic continues to distress the Indian economy across verticals and sectors, including the entertainment industry. These sectors have been witnessing massive disruptions over the past few months across the consumer value chain. Due to the increase in complexities in living standards, individuals are exploring alternatives for entertainment. Less available time for family, more workload during weekends, less vacation is some of the factors people are staying away from vising cinema halls. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…7 Khalique, A., Rahmani, M. K. I., Saquib, M., Hussain, I., Muzaffar, A. W., Ahad, M. A., … Ahmad, M. W. (2022), "A Deterministic Model for Determining Degree of Friendship Based on Mutual Likings and Recommendations on OTT Platforms "revealed that mutual likings and degree of friendship information are beneficial in recommending movies on an OTT platform. 8 Rajpal, R., Sharma, S., Goel, A., Ghosh, K., & Sharma, S. ( 2022 this study that Covid 19 pandemic has definitely acted as a catalyst having 60% respondents stating that they have started using OTT after the pandemic. 10 ISLAM, M. (2022), "Causality Exploration of Paradigm shift in people preferences to OTT Platforms during pandemic: A Mixed Study", showed that OTT platforms are leading the way in terms of people's preferences, while multiplexes have lost their way.…”
Section: Literature Reviewmentioning
confidence: 79%
“…7 Khalique, A., Rahmani, M. K. I., Saquib, M., Hussain, I., Muzaffar, A. W., Ahad, M. A., … Ahmad, M. W. (2022), "A Deterministic Model for Determining Degree of Friendship Based on Mutual Likings and Recommendations on OTT Platforms "revealed that mutual likings and degree of friendship information are beneficial in recommending movies on an OTT platform. 8 Rajpal, R., Sharma, S., Goel, A., Ghosh, K., & Sharma, S. ( 2022 this study that Covid 19 pandemic has definitely acted as a catalyst having 60% respondents stating that they have started using OTT after the pandemic. 10 ISLAM, M. (2022), "Causality Exploration of Paradigm shift in people preferences to OTT Platforms during pandemic: A Mixed Study", showed that OTT platforms are leading the way in terms of people's preferences, while multiplexes have lost their way.…”
Section: Literature Reviewmentioning
confidence: 79%